THE PORTRAYAL OF RURAL LIFE IN AUGUSTUS BALDWIN LONGSTREET’S THE FIGHT - Rezky Khoirina Tarihoran (LP2M Universitas Muslim Nusantara Al Washliyah, 2016)
This study is the result of literary research which focuses on the portrayal of rural life in Georgia during the early nineteenth century in the short story The Fight written by AB Longstreet. This research focuses on the story by the author using humorous way to depict the given circumstances. This study was conducted by applying qualitative method and analysed by using the Expreesive theory by MH Abrams. The result of this study shows that : 1) The spirit of Nationalism appeared implicitly in that story through the idea of militia, 2) The language that used by the characters also indicates how the situation was 3) The narration indicates that Georgia at that time is more developed than other counties since their religion and education had spread well in the county for that barbaric act was rarely happen.